Method and system for networking odor diffusion devices - LANGTON DAVID L; PATSTONE CHRISTOPHER H; CONROY THOMAS A; BECKER TODD H (2021)
Aspects of the present disclosure include a method of managing odors in an environment. The method includes: disposing at least one odor diffusion device within an environment, where the at least one odor diffusion device includes a communication facility that enables transmission and reception of signals to and from a remote computer; receiving, at the remote computer, at least one target value for an odor parameter of the environment; and controlling, by the remote computer, diffusion of a liquid from a source of the liquid in fluid communication with the at least one odor diffusion device to achieve the target value of the odor parameter. Controlling the diffusion rate of the liquid includes altering at least one of a voltage and a duty cycle applied to at least one component of the diffusion device. 本公开的方面包括一种管理环境中的气味的方法，其包括：将至少一个气味扩散装置设置在环境内，其中所述至少一个气味扩散装置包括通信设施，其使得能够向远程计算机发射信号和从其接收信号；在所述远程计算机处接收所述环境的气味参数的至少一个目标值；以及通过所述远程计算机控制液体从与所述至少一个气味扩散装置流体连通的所述液体的源的扩散，以达到所述气味参数的所述目标值。控制所述液体的扩散速率包括：更改施加到所述扩散装置的至少一个部件